2005
DOI: 10.1074/jbc.m504523200
|View full text |Cite
|
Sign up to set email alerts
|

A NIMA-related Protein Kinase Is Essential for Completion of the Sexual Cycle of Malaria Parasites

Abstract: The molecular mechanisms regulating the sexual development of malaria parasites from gametocytes to oocysts in their mosquito vector are still largely unexplored. In other eukaryotes, NIMA-related kinases (Neks) regulate cell cycle progression and have been implicated in the regulation of meiosis. Here, we demonstrate that Nek-4, a new Plasmodium member of the Nek family, is essential for completion of the sexual cycle of the parasite. Recombinant Plasmodium falciparum Nek-4 possesses protein kinase activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(156 citation statements)
references
References 46 publications
8
146
0
2
Order By: Relevance
“…berghei resulted in male sterility and blocked fertilization (Hirai et al ., 2008; Liu et al ., 2008). Following gamete fusion, nuclear fusion ensues, and over the next 3 h, meiosis occurs, and the zygote becomes tetraploid (Janse et al ., 1986), a process involving the NIMA‐related kinases Nek‐2 and Nek‐4 (Reininger et al ., 2005, 2009). Parasite tetraploidy persists throughout the ookinete stage until sporozoite budding in the oocyst restores the haploid state (Janse et al ., 1986) (Table 1).…”
Section: The Formation Of Gametesmentioning
confidence: 99%
“…berghei resulted in male sterility and blocked fertilization (Hirai et al ., 2008; Liu et al ., 2008). Following gamete fusion, nuclear fusion ensues, and over the next 3 h, meiosis occurs, and the zygote becomes tetraploid (Janse et al ., 1986), a process involving the NIMA‐related kinases Nek‐2 and Nek‐4 (Reininger et al ., 2005, 2009). Parasite tetraploidy persists throughout the ookinete stage until sporozoite budding in the oocyst restores the haploid state (Janse et al ., 1986) (Table 1).…”
Section: The Formation Of Gametesmentioning
confidence: 99%
“…The roles of individual protein kinases were first investigated following a reverse genetics approach in the rodent malaria model Plasmodium berghei. This revealed essential functions of a MAPK (Pbmap-2) and a CDPK (PbCDPK4) in male gametogenesis [29,46,47], of two NIMA-related kinases in meiosis in the mosquito vector [48,49], and of a CDK in asexual proliferation in erythrocytes [50]. This approach culminated in a kinome-wide study demonstrating that 23 P. berghei ePKs are redundant for asexual erythrocytic parasite development in mice and identifying phenotypes in sexual development for a number of these 23 ePKs [51].…”
Section: E C To C a R P U S S Il Ic U Lo S U S T H A L A S S I O S I mentioning
confidence: 99%
“…The expansion of the NEK family is seen to a lesser extent in Trichomonas vaginalis [83] and trypanosomes [93], which are also parasitic excavates with elaborate flagellar systems. Three of the four Plasmodium NEK family members are expressed predominantly in sexual stages [48,49,94], which include the only flagellated cell form in the Plasmodium life cycle, the male gamete; however, only one Pfnek has been clearly shown to be male-specific [95,96], whereas two others are associated with female development and appear to be involved in meiosis [48,49].…”
Section: !)mentioning
confidence: 99%
“…Interestingly, the orthologue in P. falciparum, Pfmap-2, is required for asexual growth (Dorin-Semblat et al, 2007). The initial steps of sporogony following fertilisation in P. berghei require Pbnek-4, a NIMA-related kinase with a role in meiosis (Reininger et al, 2005), and a second enzyme of this family was recently shown to also be essential for meiosis in both P. berghei and P. falciparum (Reininger et al, 2009). PbCDPK3 is required for traversal of the mosquito midgut epithelium (Ishino et al, 2006;SidenKiamos et al, 2006).…”
Section: Protein Kinases (Pks)mentioning
confidence: 99%
“…The protein kinases CDPK4 and Pbmap-2 have been associated with the production of male gametes (Billker et al, 2004;Khan et al, 2005;Rangarajan et al, 2005), Pbnek-4 and Pbnek-2 with ookinete maturation (Reininger et al, 2005;Reininger et al, 2009), and PbCDPK3 and guanylate cyclise beta with ookinete physiology (Ishino et al, 2006;SidenKiamos et al, 2006;Hirai et al, 2006). The role of signalling molecules in several other phases of sexual differentiation is however completely unknown, despite the fact that some of these processes, such as the establishment of the gametocyte parasitophorous vacuole, or gamete emergence are intrinsically complex cellular rearrangements, which proceed in response to specific cellular and environmental signals.…”
Section: A B Sexual Developmentmentioning
confidence: 99%